Aristotle's Meteorology in the Arabico-Latin Tradition : A Critical Edition of the Texts, with Introduction and Indexes - Schoonheim, Pieter L. (Aristoteles Semitico-Latinus, 2000)
Aristotle's Meteorology : a twin set in Mediaeval Text Tradition. The Greek text of Aristotle's Meteorology is in places highly problematic. Its edition by Fobes (1922), however, is a highlight in editorial technique. The Arabic version (c.800) is of quite different form and content. The two editions by Badawi (1961) and Petraitis (1967) were subject to considerable improvement. The present edition was done on the basis of the two extant Arabic manuscripts. The edition of the Latin translation (12th c.) from the Arabic has been constituted on the basis of 5 manuscript sources, out of 110 copies. The status of both the Arabic and the Latin texts was bad, but not hopeless: as the Latin version stands near to its Arabic predecessor, the text of the latter gives support to the editing of the text, as well as for the understanding of the contents. And this procedure works vice versa. The present edition of the texts has been completed with an Index of technical terms in Arabic, Greek and Latin and Registers on the Greek and Latin. Further a Bibliography and List of Latin manuscripts are presented.